Study of Si-Based GeSn Optically Pumped Lasers With Micro-Disk and Ridge Waveguide Structures - Du, Wei; Thai, Quang M.; Chrétien, Jeremie; Bertrand, Mathieu; Casiez, Lara; Zhou, Yiyin; Margetis, Joe; Pauc, Nicolas; Chelnokov, Alexei; Reboud, Vincent; Calvo, Vincent; Tolle, John; et al. (Frontiers in Physics, 2019)
Silicon-based monolithic laser has long been desired. Recent demonstration of lasing from direct bandgap group-IV alloy GeSn has opened a completely new venue from the traditional approach of III-V integration on Si. In this paper, high-quality GeSn samples were grown using a multiple-step Sn-enhanced growth recipe with a Sn composition as high as 20.0%. The GeSn lasers based on waveguide Fabry-Pérot and micro-disk cavities have been fabricated and characterized. The ridge waveguide features better local heat dissipation while the micro-disk offers stronger optical confinement as well as strain relaxation. The maximum operating temperature of 260 K from a waveguide laser and a threshold of 108 kW/cm2 at 15 K from a micro-disk laser were achieved. The peak lasing wavelength was obtained up to 3.5 µm with a 100-µm-wide ridge waveguide laser.